Narratives of pleasure and suffering at work: impacts on worker health - Almeida, Hariane Freitas Rocha (2022)
Objective: This present aimed to discuss the impacts of suffering at work on workers' health. For this, the following specific objectives were established: a) to characterize the work context; b) identify the factors that, in the workers' perception, imply in the genesis of pleasure and suffering at work and c) describe the strategies for coping with suffering. Methodology: This is a qualitative, analytical research, carried out with fifteen workers from a beverage industry located in a capital in northeastern Brazil, using thematic analysis and relying on dialectical hermeneutics. Results: The results indicated that workers experience pleasure and suffering at work, with suffering being the most present experience. There is a conscious confrontation of suffering, explained through defensive strategies and subjective mobilization that mobilize and transform some aspects of work, but which have not yet managed to change the work context. Final Considerations: The narratives supported by vulnerable employees are that the company is good for family members, as it has benefits that guarantee social and family security, but it is not evaluated as good for the worker, due to the pressure and psychological strain suffered during a day of work. And, despite recognizing the physical and psychological impacts related to work, the fear of retaliation, insecurity about professional secrecy and the low credibility of the tele-psychological care provided by the company, are the main impasses in terms of psychological assistance.